Widow's wreath : [large type] a Martha's Vineyard mystery - Riggs, Cynthia (Riggs, Cynthia. Martha's Vineyard mysteries., 2019)
A wedding on picturesque Martha's Vineyard promises to be the affair of the season when Penny Arbuthnot asks her cousin, feisty 92-year-old poet Victoria Trumbull, if she can use her property for the reception. Victoria agrees--but she has no idea what's in store for the hapless couple. For one, Penny is seriously in debt and desperate to marry money. She thinks she's on the road to riches when she hooks Rocco Bufano, whose father is a multi-billionaire. But unbeknownst to Penny, Rocco's been disowned by dad. He's also in hock up to his ears, and thinks he's bagged the catch of a lifetime in a wealthy Vineyard native. He also knows that someone is out to kill him. In fact, several guests have a reason to off Rocco, among them an autistic savant with a prodigious knowledge of murder weapons. Victoria has assumed the reception will be a modest lemonade-and-gingersnap affair--but when a body is found in her cellar, it may be a happily-never-after in Widow's Wreath, the fourteenth engaging installment in Cynthia Riggs's beloved Martha's Vineyard mysteries. This is part of "A Martha's Vineyard Mystery" series.